Nivel de satisfacción de los clientes del Hospital General Martin Icaza de la Ciudad de Babahoyo - Naranjo Yance, Anthony Nelson (2019)
This case study aims to guide the improvement of the General Martin Icaza hospital service since it deals with a common problem in this institution, the purpose of the hospital is to provide care to the inhabitants of the province of Los Ríos, however this is not It has fully complied because the level of attention does not meet the needs of users. According to (Vacarezza & Álvarez, 2011) it defines levels of attention as an orderly and stratified way of organizing resources to meet the needs of the population. The needs to be met cannot be seen in terms of services provided, but in terms of the health problems that are resolved. Among the main causes of involvement within the organization, one of the variables is the lack of commitment of the person since they do not comply with what the community or users require, that is, the low interest of the workers who exercise in it, causing In this way undue attention to users